Business Process Modeling and Prototype Development for a Digital Custom Batik Ordering System - Mahendi Putri Dinanti; Chanifah Indah Ratnasari (Komunitas Dosen Indonesia, 2025)
Manual ordering practices pose significant challenges for many craft-based small enterprises in Indonesia, including batik producers, where customer interactions, documentation, and production tracking remain largely informal. These fragmented processes result in inconsistencies, limited data access, and coordination difficulties, particularly in custom-order workflows involving multiple approval stages. This study seeks to redesign Batik Aryu’s ordering system, develop a user-centered prototype, and evaluate its user experience to assess the impact of digitalization on operational efficiency and service quality. The methodology combines Business Process Model and Notation (BPMN) for workflow analysis, evolutionary prototyping for iterative system design, and the User Experience Questionnaire (UEQ) to evaluate perceptions from both customers and administrators. BPMN analysis identified key bottlenecks in the existing manual process, leading to the development of a streamlined digital workflow that improves traceability and communication. The prototype underwent refinement through iterative feedback from the business owner, five administrative staff, and seventeen customers. UEQ results revealed varying perceptions: administrators rated most dimensions as Below Average, while Efficiency was rated as Above Average and Novelty as Good; customers rated Efficiency as Excellent, with Attractiveness and Novelty classified as Good. These findings highlight the effectiveness of the digital system in enhancing customer-facing processes, though administrative usability requires further refinement. This study contributes to the growing body of SME digitalization literature by providing an actionable framework that integrates BPMN, evolutionary prototyping, and UEQ for digital transformation, with recommendations for backend integration and real-world testing.